Effects of alkali solutions on corrosion durability of geopolymer concrete - Shaikh, Faiz (Technopress, 2014)
This paper presents chloride induced corrosion durability of reinforcing steel in geopolymer concretes containing different contents of sodium silicate (Na2SiO3) and molarities of NaOH solutions. Seven series of mixes are considered in this study. The first series is ordinary Portland cement (OPC) concrete and is considered as the control mix. The rest six series are geopolymer concretes containing 14 and 16 molar NaOH and Na2SiO3 to NaOH ratios of 2.5, 3.0 and 3.5. In each series three lollypop specimens of 100 mm in diameter and 200 mm in length, each having one 12 mm diameter steel bar are considered for chloride induced corrosion study. The specimens are subjected to cyclic wetting and drying regime for two months. In wet cycle the specimens are immersed in water containing 3.5% (by wt.) NaCl salt for 4 days, while in dry cycle the specimens are placed in open air for three days. The corrosion activity is monitored by measuring the copper/copper sulphate (Cu/CuSO4) half-cell potential according to ASTM C-876. The chloride penetration depth and sorptivity of all seven concretes are also measured. Results show that the geopolymer concretes exhibited better corrosion resistance than OPC concrete. The higher the amount of Na2SiO3 and higher the concentration of NaOH solutions the better the corrosion resistance of geopolymer concrete is. Similar behaviour is also observed in sorptivity and chloride penetration depth measurements. Generally, the geopolymer concretes exhibited lower sorptivity and chloride penetration depth than that of OPC concrete. Correlation between the sorptivity and the chloride penetration of geopolymer concretes is established. Correlations are also established between 28 days compressive strength and sorptivity and between 28 days compressive strength and chloride penetration of geopolymer concretes.